2017
DOI: 10.1016/j.apsusc.2017.06.221
|View full text |Cite
|
Sign up to set email alerts
|

rGO-ZnO nanocomposites for high electrocatalytic effect on water oxidation obtained by microwave-hydrothermal method

Abstract: Reduced graphene oxide-zinc oxide (rGO-ZnO) nanocomposites were successfully synthesized using a facile microwave-hydrothermal method under mild conditions, and their electrocatalytic properties towards O 2 evolution were investigated. The microwave radiation played an important role in obtainment of well dispersed ZnO nanoparticles directly on reduced graphene oxide sheets without any additional reducing reagents or passivation agent. X-ray diffraction (XRD), Raman and infrared spectroscopies indicated the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(33 citation statements)
references
References 76 publications
0
30
0
3
Order By: Relevance
“…Microwave hydrothermal synthesis of ZnO nanocomposites or ZnO hybrid nanostructures without any additional heat treatment, where the literature review results [ 674 , 675 , 676 , 677 , 678 , 679 , 680 , 681 , 682 , 683 , 684 , 685 , 686 , 687 , 688 , 689 , 690 , 691 , 692 , 693 , 694 , 695 , 696 , 697 , 698 , 699 , 700 , 701 , 702 , 703 , 704 , 705 , 706 , 707 , 708 , 709 , 710 , 711 , 712 , 713 , 714 , 715 , 716 , 717 , 718 , 719 ,…”
Section: Microwave Hydrothermal Synthesis Of Znomentioning
confidence: 99%
“…Microwave hydrothermal synthesis of ZnO nanocomposites or ZnO hybrid nanostructures without any additional heat treatment, where the literature review results [ 674 , 675 , 676 , 677 , 678 , 679 , 680 , 681 , 682 , 683 , 684 , 685 , 686 , 687 , 688 , 689 , 690 , 691 , 692 , 693 , 694 , 695 , 696 , 697 , 698 , 699 , 700 , 701 , 702 , 703 , 704 , 705 , 706 , 707 , 708 , 709 , 710 , 711 , 712 , 713 , 714 , 715 , 716 , 717 , 718 , 719 ,…”
Section: Microwave Hydrothermal Synthesis Of Znomentioning
confidence: 99%
“…The Raman spectra of GO and RGO ( Figure 6a) show D (1336 cm -1 ) and G (1590 cm -1 ) bands, corresponding to carbon-carbon vibrations that are actives in the presence of defects and Csp 2 bonds, respectively [52][53][54] . The ratio I D /I G that is an indication of defects had a value of 1.01 for GO and 1.16 for RGO, which suggests a decrease in the sp 2 domains, and confirms the reduction of GO 50 .…”
Section: Rgo and Zno Composites Characterizationmentioning
confidence: 99%
“…The ratio I D /I G that is an indication of defects had a value of 1.01 for GO and 1.16 for RGO, which suggests a decrease in the sp 2 domains, and confirms the reduction of GO 50 . Concerning to ZnO and the composites (Figure 6b), it was observed that ZnO spectrum shows peaks at 438 cm -1 , corresponding to E2 (high) mode of the wurtzite structure; at 332 cm -1 , due to 3E2H-E2L phonon mode; at 381 cm -1 , corresponding to A1T mode related to the structural order-disorder in the lattice; and at 1108 cm -1 , which corresponds to 2A1 (LO) and 2E1 (LO) modes of the Brillouin zone of ZnO 45,52,55 . The composites ZnO/GO8 and ZnO/RGO600 presented the bands of D and G vibrational modes related to GO and RGO along with the bands of the zinc oxide phase.…”
Section: Rgo and Zno Composites Characterizationmentioning
confidence: 99%
“…30 The wide band gap (3.37 eV) of ZnO makes it suitable for water oxidation since band gap energy exceeds the oxidation potential of water (1.23 eV). 31 As another n-type semiconductor, ZnS with wide band gap energy (3.5-3.7 eV) offers suitable band edge positions for H 2 evolution. 32 ZnS nanostructures were generally deposited on other nanostructures to suppress photocorrosion and enhanced the photocurrents.…”
Section: Introductionmentioning
confidence: 99%
“…33 In the literature, electrochemical/photoelectrochemical studies by using ZnO or ZnS nanostructures have been reported by researchers. The electrocatalytic properties of reduced graphene oxide-zinc oxide (rGO-ZnO) toward O 2 evolution were investigated by Romeiro et al 31 The nanocomposite material was synthesized via microwave-hydrothermal method. The formation of high electronic interaction between rGO and ZnO sheets has improved the electrocatalytic efficiency.…”
Section: Introductionmentioning
confidence: 99%